Combined analysis of the moderating effect of a GRIK1 polymorphism on the effects of topiramate for treating alcohol use disorder. (1st August 2021) - Kranzler, Henry R.; Hartwell, Emily E.; Feinn, Richard; Pond, Timothy; Witkiewitz, Katie; Gelernter, Joel; Crist, Richard C.
Highlights: In a prior study, topiramate reduced heavy drinking and a genetic variant moderated the effect. A subsequent study replicated the topiramate effect, but not the pharmacogenetic finding. We conducted a combined analysis of the two published studies to increase statistical power. The analysis showed a robust treatment effect for topiramate, but no pharmacogenetic effect. Abstract: Background: In an initial study, we reported that topiramate reduced heavy drinking among individuals who sought to reduce their drinking and that the effect was moderated by a single nucleotide polymorphism (SNP; rs2832407) in GRIK1, which encodes the kainate GluK1 receptor subunit (Kranzler et al., 2014 ). In a subsequent study that prospectively randomized patients to medication group based on their rs2832407 genotype, we replicated the main effect of topiramate but not the moderating effect of the SNP (Kranzler et al., 2021 ). Given the similar design of the two studies, here we combined the findings to provide greater statistical power to test the pharmacogenetic effect. Material and methods: This secondary analysis of two 12-week, randomized controlled trials of topiramate included a total of 292 European-ancestry individuals (67.1 % male; topiramate: 48.3 %, placebo: 51.7 %) with problematic alcohol use. Using MANOVA, we examined changes in self-reported alcohol consumption, problems resulting from alcohol use, and quality of life, and the biomarker γ-glutamyltransferase. To test the pharmacogenetic hypothesis, all patients were genotyped for rs2832407. Results: There was a significant overall effect of topiramate on the alcohol-related outcomes (partial η 2 = 0.134, p < 0.001), with follow-up analyses showing significant reductions in percent heavy drinking days (Cohen's d = 0.49), percent days abstinent (d = 0.23), drinks/day (d = 0.29) and alcohol-related problems (d = 0.45). Overall, the moderating effect of the SNP was non-significant (partial η² = 0.026, p = 0.37). Conclusions: Although topiramate is an efficacious medication for reducing drinking and alcohol-related problems among patients with problematic alcohol use, rs2832407 does not appear to moderate its therapeutic effects. www.clinicaltrials.gov registrations: NCT00626925 and NCT02371889